Discovery of 2, 3-dihydro-1H-pyrrolo[3, 4-b]quinolin-1-one derivatives as possible antileishmanial agents. Issue 6 (25th May 2022) - Seth, Anuradha; Ghoshal, Anirban; Dewaker, Varun; Rani, Ankita; Singh, Sangh Priya; Dutta, Mukul; Katiyar, Shivani; Singh, Sandeep Kumar; Rashid, Mamunur; Wahajuddin, Muhammad; Kar, Susanta; Srivastava, Ajay Kumar
Abstract : A series of uniquely functionalized 2, 3, -dihydro-1 H -pyyrolo[3, 4- b ]quinolin-1-one derivatives were synthesized in one to two steps by utilizing a post-Ugi modification strategy and were evaluated for antileishmanial efficacy against visceral leishmaniasis (VL). Abstract : A series of uniquely functionalized 2, 3, -dihydro-1 H -pyyrolo[3, 4- b ]quinolin-1-one derivatives were synthesized in one to two steps by utilizing a post-Ugi modification strategy and were evaluated for antileishmanial efficacy against visceral leishmaniasis (VL). Among the library compounds, compound 5m exhibited potential in vitro antileishmanial activity (CC50 = 65.11 μM, SI = 7.79, anti-amastigote IC50 = 8.36 μM). In vivo antileishmanial evaluation of 5m demonstrated 56.2% inhibition in liver and 61.1% inhibition in spleen parasite burden in infected Balb/c mice (12.5 mg kg −1, i.p.). In vitro pharmacokinetic study ascertained the stability of 5m in both simulated gastric fluid and simulated intestinal fluid. All the active compounds passed the PAINS filter and showed no toxicity in in silico predictions.